2017
DOI: 10.1242/jeb.151506
|View full text |Cite
|
Sign up to set email alerts
|

miR-29a modulates SCD expression and is regulated in response to a saturated fatty acids diet in juvenile GIFT (Oreochromis niloticus)

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that regulate target gene expression by binding to the 3′ untranslated region (3′ UTR) of the target mRNA. MiRNAs regulate a large variety of genes, including those involved in liver biology and disease. Here, we report for the first time that miR-29a post-transcriptionally regulates stearoyl-CoA desaturase (SCD) by binding to its 3′ UTR in genetically improved farmed tilapia (GIFT), Oreochromis niloticus, as shown by a 3′ UTR luciferase reporter assay. miR-29a anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…Antagomirs are cholesterol-conjugated single-stranded RNA molecules (21-23 nt) that complementary to the specific miRNA region with either mispairing at the cleavage of Ago2 or some varieties of base modification to inhibit Ago2 cleavages (Krutzfeldt et al, 2005). Some previous studies have revealed that the antagomirs could block the endogenous miRNA expression in cell lines, zebrafish, and tilapia (Morton et al, 2008;Selvamani et al, 2012;Qiang et al, 2017). Therefore, we also conducted this method to verify whether it would impede endogenous miR-206 expression and effect on the target Mc1r gene.…”
Section: Discussionmentioning
confidence: 99%
“…Antagomirs are cholesterol-conjugated single-stranded RNA molecules (21-23 nt) that complementary to the specific miRNA region with either mispairing at the cleavage of Ago2 or some varieties of base modification to inhibit Ago2 cleavages (Krutzfeldt et al, 2005). Some previous studies have revealed that the antagomirs could block the endogenous miRNA expression in cell lines, zebrafish, and tilapia (Morton et al, 2008;Selvamani et al, 2012;Qiang et al, 2017). Therefore, we also conducted this method to verify whether it would impede endogenous miR-206 expression and effect on the target Mc1r gene.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to regulation by upstream transcription factors, SCD-1 may be repressed through a microRNA-mediated mechanism. Recent studies have demonstrated the roles of miR-125b and miR-29a in the regulation of SCD-1[ 41 , 42 ]. In our study, we found that a region of the SCD 3’ UTR completely matched a seed sequence (5’-UGACCUA-3’) at the binding site of miR-192-5p, demonstrating a direct interaction between miR-192-5p and SCD-1.…”
Section: Discussionmentioning
confidence: 99%
“…Specific primers for miR-122 are shown in Table 1 . Extraction of miRNAs, synthesis of first-strand cDNA, and qRT-PCR analyses were conducted using the procedures described by Qiang et al (2017b) . We amplified U6 as the reference gene, using the U6 primer supplied in the miRNA SYBR Green qRT-PCR kit (Takara, Dalian, China).…”
Section: Methodsmentioning
confidence: 99%
“…In Chinese mitten crabs ( Eriocheir sinensis ) fed on fish oil, soybean oil, or a 1:1 fish oil: soybean mixture, the SCD transcript levels were 3.5-, 2-, and 1.3-times higher, respectively, than that in the control group (fed a diet containing 3% base fat) ( Guo et al, 2013 ). The addition of coconut oil (with a high proportion of SFA and a lower proportion of PUFA) to the diet significantly increased SCD transcript levels and increased lipid accumulation in hybrid tilapia ( O. aureus ♂ × O. niloticus ♀) ( Hsieh et al, 2007 ) and GIFT ( Qiang et al, 2017b ). Together, these results suggested that SCD also plays an important role in the regulation of fat metabolism in aquatic animals.…”
Section: Introductionmentioning
confidence: 99%